27. THE RESULTS OF TO TREAT GUYON'S SYNDROME SURGERY AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: The results of surgery to treat Guyon’s syndrome at Thong Nhat Hospital. Subjects and research methods: A research study was conducted in 9 patients operated on for compressive neuropathies of the ulnar nerve in the canal of Guyon at the orthopedic trauma department of Thong Nhat Hospital from 01/2019 to 01/2024. Results: Post-operative improvements in all clinical and EMG parameters were significant. All but one patient (90%) showed improvement in symptoms after surgery; on the other hand, pre-operative severe impairment of motor nerve conduction highly affected the post-operative motor function. Guyon’s canal syndrome accounted for 0.8% of all compressive neuropathies of the upper extremity in our patients. Conclusion: Syndrome of Guyon’s canal can easily be treated by surgery. As in other compression syndromes, the sooner a surgical decompression is performed, the better outcomes are achieved.
Keywords: Guyon Canal Syndrome, ulnar nerve decompression.